Mechanisms of cross-talk between the diet, the intestinal microbiome, and the undernourished host. (4th March 2017) - Velly, Helene; Britton, Robert A.; Preidis, Geoffrey A.
ABSTRACT: Undernutrition remains one of the most pressing global health challenges today, contributing to nearly half of all deaths in children under five years of age. Although insufficient dietary intake and environmental enteric dysfunction are often inciting factors, evidence now suggests that unhealthy gut microbial populations perpetuate the vicious cycle of pathophysiology that results in persistent growth impairment in children. The metagenomics era has facilitated new research identifying an altered microbiome in undernourished hosts and has provided insight into a number of mechanisms by which these alterations may affect growth. This article summarizes a range of observational studies that highlight differences in the composition and function of gut microbiota between undernourished and healthy children; discusses dietary, environmental and host factors that shape this altered microbiome; examines the consequences of these changes on host physiology; and considers opportunities for microbiome-targeting therapies to combat the global challenge of child undernutrition.